Cybersecurity in the age of smart societies: proceedings of the 14th International Conference on Global Security, Safety and Sustainability, London, September 2022 - Jahankhani, Hamid (Advanced sciences and technologies for security applictions, 2023)
This book provides an opportunity for researchers, scientists, government officials, strategist and operators and maintainers of large, complex and advanced systems and infrastructure to update their knowledge with the state of best practice in the challenging domains whilst networking with the leading representatives, researchers and solution providers. The ongoing pandemic has created a new level of threats which presents new challenges around privacy, data protection, malicious application, unprotected networks or networks with basic protection that are being used as a gateway to larger infrastructure with complicated architecture, and unintentional misuse such as those associated with algorithmic bias. All these have increased the number of attack vectors that can be used to attack such networks. Drawing on 13 years of successful events on information security, digital forensics and cyber-crime, the 14th ICGS3-22 conference aims to provide attendees with an information-packed agenda with representatives from across the industry and the globe. The challenges of complexity, rapid pace of change and risk/opportunity issues associated with modern products, systems, special events and infrastructures. In an era of unprecedented volatile, political and economic environment across the world, computer-based systems face ever more increasing challenges, disputes and responsibilities, and whilst the Internet has created a global platform for the exchange of ideas, goods and services, it has also created boundless opportunities for cyber-crime. This volume presents new materials and contribute to knowledge through the technological advances that are being made across artificial intelligence (AI), machine learning, blockchain and quantum computing. These technologies driven by a digital revolution are expected to be disruptive and provide major digital transformation in the way societies operate today. As result, although these advances provide social and economic benefits, but, also, provide new challenges that security industry need to raise their game to combat them.